(untitled) (Nativa, 2019)
A castanheira-do-brasil (Bertholletia excelsa Bonpl.) é nativa da Amazônia e importante espécie de exploração extrativista. O ambiente edáfico característico de áreas de ocorrência de concentração de populações naturais de castanheira-do-brasil, no norte de Mato Grosso foi avaliado. O estudo foi conduzido em quatro áreas de ocorrência de castanhais no norte de Mato Grosso, nos municípios de Itaúba, Alta Floresta, Juína e Cotriguaçu, nos quais se descreveu os perfis de solos, e dos quais foram feitas análises químicas, granulométricas e mineralógicas. Os resultados indicaram que a castanheira-do-brasil é espécie típica de clima predominante na Amazônia, que ocorre em solos ácidos, de textura variando de arenosa a média, de baixa fertilidade natural e, às vezes, com elevado teor de alumínio, entretanto, são solos cauliníticos ou cauliníticos-gibbsíticos, o que os difere da maioria dos solos de cerrados. Foram identificados solos dos grandes grupos Argissolo Vermelho Amarelo distróficos e Latossolo Vermelho Amarelo distróficos de relevo plano a ondulado. Palavras-chave: solos florestais, perfil de solo, atributos químicos, pedomorfologia, mineralogia. PEDOLOGICAL CHARACTERIZATION AT PLACES OF OCCURRENCE OF NATURAL POPULATIONS OF BRAZIL NUTS IN THE STATE OF MATO GROSSO ABSTRACT: The Brazil nuts trees (Bertholletia excels Bonpl.) are native to the Amazon and important specie of extractive exploitation. The edaphic environment characteristic of concentration areas of Brazil nuts tree specimens, in the North of Mato Grosso was evaluated in research project that studied the edaphic attributes at places of occurrence of natural populations of Brazil nuts in the State of Mato Grosso. The study was carried out in four areas of Brazil nuts occurrence in the North of Mato Grosso, in the municipalities of Itaúba, Alta Floresta, Juína and Cotriguaçu, which described the soil profiles, and which were made chemical, physical and mineralogical analysis. The results indicated that the Brazil nuts tree is a typical specie of the Amazon, which grows in the State of Mato Grosso, in soils acids, ranging from sandy to loamy texture, low natural fertility and, sometimes, with high content of aluminum, however, is a caullinitic or caullinitic-gibbsitic soils, which differs from the majority of soils of the Brazilian savanna. Soils were identified as dystrophic Red Yellow Argisols (Haplustult) and Red Yellow Latosols (Haplustox) and relief vary from plain to undulate. Keywords: forest soils, soil profile, chemical attributes, morphological attributes, mineralogy.